Microbiota determines insulin sensitivity in TLR2-KO mice - Guadagnini, Dioze; Rocha, Guilherme Zweig; Santos, Andrey; Assalin, Heloisa Balan; Hirabara, Sandro Massao; Curi, Rui; Oliveira, Alexandre Gabarra [UNESP]; Prada, Patricia O.; Saad, Mario J.A. (Elsevier, 2019)
Introduction: Environmental factors have a key role in the control of gut microbiota and obesity. TLR2 knockout (TLR2−/−) mice in some housing conditions are protected from diet-induced insulin resistance. However, in our housing conditions these animals are not protected from diet-induced insulin-resistance. Aim: The aim of the present study was to investigate the influence of our animal housing conditions on the gut microbiota, glucose tolerance and insulin sensitivity in TLR2−/− mice. Material and methods: The microbiota was investigated by metagenomics, associated with hyperinsulinemic euglycemic clamp and GTT associated with insulin signaling through immunoblotting. Results: The results showed that TLR2−/− mice in our housing conditions presented a phenotype of metabolic syndrome characterized by insulin resistance, glucose intolerance and increase in body weight. This phenotype was associated with differences in microbiota in TLR2−/− mice that showed a decrease in the Proteobacteria and Bacteroidetes phyla and an increase in the Firmicutesphylum, associated with and in increase in the Oscillospira and Ruminococcus genera. Furthermore there is also an increase in circulating LPS and subclinical inflammation in TLR2−/−. The molecular mechanism that account for insulin resistance was an activation of TLR4, associated with ER stress and JNK activation. The phenotype and metabolic behavior was reversed by antibiotic treatment and reproduced in WT mice by microbiota transplantation. Conclusions: Our data show, for the first time, that the intestinal microbiota can induce insulin resistance and obesity in an animal model that is genetically protected from these processes.
Keywords: Genetic protection; Gut microbiota; Insulin resistance; LPS; TLR2